ANALISIS PREFERENSI MASYARAKAT TERHADAP KUALITAS PELAYANAN RUMAH SAKIT - PUTRI, DINI AMALIA; SUKARSA, I KOMANG GDE; JAYANEGARA, KETUT (E-Jurnal Matematika; Vol 8 No 3 (2019)DO - 10.24843/MTK.2019.v08.i03.p256, 2019)
Conjoined analysis is a multivariate technique specifically developed to get people's preferences. The purpose of this study is to determine people's preferences for the quality of hospital services based on attributes to determine the combination of these attributes that are most desired by customers. This study uses primary data taken through surveys using a questionnaire. The survey conducted at Udayana Denpasar Hospital was applied with non-probability sampling techniques, namely accidental sampling with the number of samples needed was 100 respondents. The attributes used in this study were (a) physician services, (b) number of patients, (c) facilities, (d) location of the bathroom, and (e) price. The results showed that the most valued attribute by respondents was Facility. The combination of the level of each attribute that most influences the respondents in determining the room when doing hospitalization at the Level II Hospital of Udayana Denpasar is handled by a Specialist, consisting of 1 patient, bathroom, with facilities consisting of tv, air conditioning, refrigerator, cupboard , buffet, sofa, table, living room and bed for the patient's family, with a price of> 1,000,000.